Assessing Change Over Time in Voice Handicap and Voice-Related Perceived Control Using Ecological Momentary Assessment. (September 2019) - Nguyen-Feng, Viann N.; Frazier, Patricia A.; Stockness, Ali; Lunos, Scott; Hoedeman, Alexis N.; Misono, Stephanie
Objectives: Voice handicap has generally been measured at a single timepoint. Little is known about its variability from hour to hour or day to day. Voice handicap has been shown to be negatively related to voice-related perceived control in cross-sectional studies, but the within-person variability in voice-related perceived control is also unknown. We aimed to use ecological momentary assessment (EMA) to (1) assess the feasibility of EMA to examine daily voice handicap and voice-related perceived control in patients with voice disorders, (2) measure within-person variability in daily voice handicap and perceived control, and (3) characterize temporal associations (eg, correlations over time) between daily voice handicap and perceived control. Methods: Adults with voice problems were recruited from a large public university medical center in the Midwest. They completed baseline measures, followed by twice-daily assessments, including selected items measuring voice handicap and perceived control, and then repeated the baseline measures at the final timepoint. Feasibility was assessed via completion rates. Within-person variability was measured using standard deviations. Temporal associations were characterized using simulation modeling analysis. Results: EMA of voice handicap and perceived control was feasible in this patient population. Momentary voice handicap varied more than perceived control, though both were variable. Multiple patterns of temporal associations between daily voice handicap and perceived control were found. Conclusions: These findings identified important variability in (1) measures of voice handicap and perceived control and (2) their associations over time. Future EMA studies in patients with voice disorders are both feasible and warranted.